Mobile ions determine the luminescence yield of perovskite light-emitting diodes under pulsed operation - Naresh Kumar Kumawat (Nature Portfolio, 2021)
Pulsed operation of perovskite light-emitting diodes is of particular importance in display and visible light communication, yet the ionic behaviour under this mode is not well-understood. Here, the authors reveal that the transient electroluminescence intensity increases with increasing pulse width as the result of accumulation of mobile ions at the interfaces.